A new false truffle species, Gautieria zixishanensis sp. nov. (Gomphales, Basidiomycota) found in Yunnan, China - Li, Lin; Wan, Shanping; Thongklang, Naritsada; Liu, Qiongbo; Luo, Zonglong; Tang, Songming; Zhou, Ying; Li, Shuhong; Hyde, Kevin D. (Phytotaxa, 2025)
A new species of false truffle was discovered in Zixishan Mountain, Yunnan Province, China. Through morphological examination and multigene phylogenetic analysis based on ITS and nrLSU sequences of the genus Gautieria, the species is described as Gautieria zixishanensis sp. nov., belonging to Gautieria sect. Hymenogastroides. This new species is characterized by its pseudoperidial basidiomata, with a basal depression connected to abundant white basal rhizomorphs, an intact tomentose pseudoperidium that remains attached when mature, the absence of foveate-porate structures and ridges, and light golden-brown basidiospores with longitudinal ridges, measuring 17–22 μm in length.